Investigation of Intentional, Habitual and Self-regulatory Mechanisms in Health and Environmental Behaviours - Dorina, Indita (Curtin University, 2024)
The overarching aim of this thesis was to test the utility of temporal self-regulation theory in predicting behaviour. Specifically, I explored the role and importance of intentional, habitual, and self-regulatory processes across a range of health and environmental behaviours. Overall, findings from four studies provide partial support for the theory. However, more research, particularly regarding self-regulation, is needed to inform application of the theory in future research, as well its application in behaviour changes interventions.